Field evidence for colour mimicry overshadowing morphological mimicry. Issue 3 (20th December 2020) - Corral‐Lopez, Alberto; Varg, Javier Edo; Cano‐Cobos, Yiselle P.; Losada, Rafael; Realpe, Emilio; Outomuro, David
Abstract: Imperfect mimicry may be maintained when the various components of an aposematic signal have different salience for predators. Experimental laboratory studies provide robust evidence for this phenomenon. Yet, evidence from natural settings remains scarce. We studied how natural bird predators assess multiple features in a multicomponent aposematic signal in the Neotropical 'clear wing complex' mimicry ring, dominated by glasswing butterflies. We evaluated two components of the aposematic signal, wing colouration and wing morphology, in a predation experiment based on artificial replicas of glasswing butterflies (model) and Polythoridae damselflies (mimics) in their natural habitat. We also studied the extent of the colour aposematic signal in the local insect community. Finally, we inspected the nanostructures responsible for this convergent colour signal, expected to highly differ between these phylogenetically distinct species. Our results provide direct evidence for a stronger salience of wing colouration than wing morphology, as well as stronger selection on imperfect than in perfect colour mimics. Additionally, investigations of how birds perceive wing colouration of the local insect community provides further evidence that a UV‐reflective white colouration is being selected as the colour aposematic signal of the mimicry ring. Using electron microscopy, we also suggest that damselflies have convergently evolved the warning colouration through a pre‐adaptation. These findings provide a solid complement to previous experimental evidence suggesting a key influence of the cognitive assessment of predators driving the evolution of aposematic signals and mimicry rings. Abstract : This work is one of the first studies testing signal overshadow in the field, being an important contribution to our understanding of mimicry evolution. The authors results suggest that colour overshadows morphology, but imperfect colour mimics seem to be under stronger predator selection than perfect colour mimics. They also explore the colour aposematic signal in the local insect community, as well as the nanostructures responsible for the production of such convergent cue in phylogenetically distant species.